Baseline features of the VICTORIA (Vericiguat Global Study in Subjects with Heart Failure with Reduced Ejection Fraction) trial. (9th December 2019) - Pieske, Burkert; Patel, Mahesh J.; Westerhout, Cynthia M.; Anstrom, Kevin J.; Butler, Javed; Ezekowitz, Justin; Hernandez, Adrian F.; Koglin, Joerg; Lam, Carolyn S.P.; Ponikowski, Piotr; Roessig, Lothar; Voors, Adriaan A.; et al.
Abstract : Aim: Describe the distinguishing features of heart failure (HF) patients with reduced ejection fraction (HFrEF) in the VICTORIA (Vericiguat Global Study in Patients with Heart Failure with Reduced Ejection Fraction) trial. Methods and results: Key background characteristics were evaluated in 5050 patients randomized in VICTORIA and categorized into three cohorts reflecting their index worsening HF event. Differences within the VICTORIA population were assessed and compared with PARADIGM‐HF (Prospective comparison of ARNI with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure) and COMMANDER HF (A Study to Assess the Effectiveness and Safety of Rivaroxaban in Reducing the Risk of Death, Myocardial Infarction, or Stroke in Participants with Heart Failure and Coronary Artery Disease Following an Episode of Decompensated Heart Failure). VICTORIA patients had increased risk of mortality and rehospitalization: New York Heart Association class (40% class III), atrial fibrillation (45%), diabetes (47%), hypertension (79%) and mean estimated glomerular filtration rate of 61.5 mL/min/1.73 m 2 . Baseline standard of HF care was very good: 60% received triple therapy. Their N‐terminal pro‐B‐type natriuretic peptide was 3377 pg/mL [interquartile range (IQR) 1992–6380]. Natriuretic peptides were 30% higher level in the 67% patients with HF hospitalization <3 months, compared to those within 3–6 months of HF hospitalization and those randomized after recent outpatient intravenous diuretic therapy. Overall the median MAGGIC (Meta‐Analysis Global Group in Chronic Heart Failure) risk score in VICTORIA was 23 (IQR 18–27) as compared to the MAGGIC risk score in PARADIGM‐HF of 20 (IQR 16–24). Conclusions: VICTORIA comprises a broadly generalizable high‐risk population of three unique clinical strata of worsening chronic HFrEF despite very good HF therapy. VICTORIA will establish the role of vericiguat, a soluble guanylate cyclase stimulator, in HFrEF.